PENTINGNYA PENDIDIKAN NILAI UNTUK MEMBENTUK KEPRIBADIAN GEN Z DI ERA DIGITAL - Addina Maghfirah; Yakobus Ndona, Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Generation Z is the generation born between 1995 and 2010 and is known as the iGeneration or the internet generation because their lives are closely connected to digital technology. Easy access to information and culture from outside brings positive impacts, but also has the potential to cause negative impacts if not balanced with adequate value instillation. Therefore, value education is crucial to shape the personality of Gen Z so that they are able to utilize technology wisely while maintaining the nation's noble values. This study aims to determine the urgency of value education for Generation Z in the digital era. The research method used is a literature study by reviewing articles, journals, and other relevant sources, then the data is analyzed based on thematic studies. The results show that value education plays a strategic role in instilling honesty, responsibility, discipline, cooperation, and tolerance, so that Gen Z not only develops intellectually, but also has a moral personality, culture, and strong character. Thus, value education is very urgent to create a resilient generation and able to make a positive contribution to the nation amidst the rapid flow of digitalization.